Il rizoma e il cristallo. Deleuze da Mille piani a Immagine-tempo, e ritorno - Angelucci, Daniela (Scenari, 2024)
The article aims to make explicit the link between Deleuze’s two books on cinema and the immediately preceding volume, A Thousand Plateaus (1980), the second volume after Anti-Edipus (1972) of the project written four-handedly with Guattari, with the overall title Capitalism and Schizophrenia. The connection between the figure of the rhizome, a term borrowed from botany and reinvented by the two authors to describe the movement of being in a theory of immanence, and that of the crystal, i.e. the point of indiscernibility between matter and memory in books on cinema, will be particularly highlighted. The task the two figures share is to propose a philosophy of immanence, anti-substantialist and anti-humanist.